Arbutus unedo L. as an alternative source of anthocyanin compounds for application as food colouring agent - Pereira, Carla (2018)
Arbutus unedo L., commonly known as strawberry-tree, is a shrub used as ornamental plant in the gloomy Mediterranean areas which fruits are popularly eaten and used to produce beverages . Beyond these common applications, these fruits could also be explored for their phenolic composition, once they are a source of anthocyanin compounds with great colouring capacity to be potentially used in food industry, in detriment of artificial colorants. In this context, the present study aimed to optimize the extraction of these compounds from A. unedo fruits through different techniques, namely heat and ultrasound assisted extraction and, for that purpose, a response surface methodology was applied using the circumscribed central composite design of three variables with five levels. For the model application, the anthocyanin concentration and the extraction yield were used as responses, being the identification of these compounds performed by HPLC-DAD-ESI/MS. The anthocyanin profile of A. unedo fruits consisted of delphinidin-3-glucoside, cyanidin-3-glucoside, and cyanidin-3-pentoside, with cyanidin-3-glucoside as the most abundant one. Heat assisted extraction proved to be the most effective technique at 5 min, 90°C, and 80% of ethanol, yielding 51.2% of fruit dry weight, with a total anthocyanin concentration of 382.4 μg/g of dried fruit, and 744.6 μg/g of extract. Moreover, these response values were slightly improved by studying the solid/liquid ratio effect at the optimal conditions indose-response format, showing steady extraction values from 5 to 40 g/L. The obtained results showed the possibility of using A. unedo fruits as a source of anthocyanin compounds for industrial applications.